Provision of acute stroke care and associated factors in a multiethnic population: prospective study with the South London Stroke Register. (24th February 2011) - Addo, Juliet; Bhalla, Ajay; Crichton, Siobhan; Rudd, Anthony G; McKevitt, Christopher; Wolfe, Charles D A
Abstract : Objectives To investigate time trends in receipt of effective acute stroke care and to determine the factors associated with provision of care. Design Population based stroke register. Setting South London. Participants 3800 patients with first ever ischaemic stroke or primary intracerebral haemorrhage registered between January 1995 and December 2009. Main outcome measures Acute care interventions, admission to hospital, care on a stroke unit, acute drugs, and inequalities in access to care. Results Between 2007 and 2009, 5% (33/620) of patients were still not admitted to a hospital after an acute stroke, particularly those with milder strokes, and 21% (124/584) of patients admitted to hospital were not admitted to a stroke unit. Rates of admission to stroke units and brain imaging, between 1995 and 2009, and for thrombolysis, between 2005 and 2009, increased significantly (P<0.001). Black patients compared with white patients had a significantly increased odds of admission to a stroke unit (odds ratio 1.76, 95% confidence interval 1.35 to 2.29, P<0.001) and of receipt of occupational therapy or physiotherapy (1.90, 1.21 to 2.97, P=0.01), independent of age or stroke severity. Patients with motor or swallowing deficits were also more likely to be admitted to a stroke unit (1.52, 1.12 to 2.06, P=0.001 and 1.32, 1.02 to 1.72, P<0.001, respectively). Length of stay in hospital decreased significantly between 1995 and 2009 (P<0.001). The odds of brain imaging were lowest in patients aged 75 or more years (P=0.004) and those of lower socioeconomic status (P<0.001). The likelihood of those with a functional deficit receiving rehabilitation increased significantly over time (P<0.001). Patients aged 75 or more were more likely to receive occupational therapy or physiotherapy (P=0.002). Conclusion Although the receipt of effective acute stroke care improved between 1995 and 2009, inequalities in its provision were significant, and implementation of evidence based care was not optimal.